HUMAN KINETICS: ALOOK AT THE BODYIN PHYSICALEDUCATION SCHOOL (Fiep Bulletin - online, 2012)
The historical course of education in the body and the possibilities of the human movement in physicaleducation is what motivates us to write this essay. The body currently is the object of mass requirement of theaesthetic. The school through the human movement can provide in addressing the content of physical education,a position to contribute to young people to develop greater respect for your body. The human being is subjectivityand only by becoming aware of his situation, can counteract the charge to model the body according to the will ofanother. The way of questioning during the operation of content enables the decision-making and critical positionin situations that require some action. For this pedagogical exercise, the teachers contribute decisively to build afull and harmonious human development through an embodiment and perceived living.